Muhammadiyah Sebagai Gerakan Islam, Dakwah dan Tajdid - Anugrah Giffari Syukri Rahman; Muhammad Hayat (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
Founded in 1912 by K.H. Ahmad Dahlan, Muhammadiyah is one of the world's largest modernist Islamic organizations. Its enduring and massive influence for over a century is rooted in the synergy of three identity pillars: Islam, Da'wah, and Tajdid. This article analyzes how the integration of these pillars shapes Muhammadiyah's ideology and strategy, arguing that its strength lies in the dynamic dialectic among the three, rather than in any single one. As an Islamic movement, Muhammadiyah emphasizes the purification of creed (aqidah) through the slogan "returning to the Qur'an and Sunnah," while rejecting superstition, heretical innovations, and myths. As a Da'wah movement, it pioneers the da'wah bil-hal approach (preaching through deeds), materialized by establishing thousands of educational, health, and social institutions as a manifestation of its "Theology of Al-Ma'un." As a Tajdid (renewal) movement, Muhammadiyah consistently integrates two dimensions: purification in the realm of ritual worship (ibadah mahdhah) and dynamization-modernization in worldly affairs (muamalah dunyawiyah). This synergy of the three pillars is what forges Muhammadiyah's identity as a movement of "Progressive Islam," making it perpetually relevant, adaptive, and a significant contributor to Indonesian society and the world.